Skip to Content
Jul 14, 2010 at 06:28 AM

dynamic assignment in expression


Hi Friends,

I have a requirement such that, based on some conditions, a = b + c, or a = b + d, or a = a - c, or a = a + c, and so on... All variables are of currency type (13,2).

Now, the logic of this condition-based equation comes from table ( i.e. if a = a - c, then 'a' , '-' and 'c' are maintained in a custom table).

I want to populate a text by concatenating 'a' '-' 'c' such that the text equals 'a - c'. Now I want to equate a with text (a = text )to get the value as that of (a - c).

If you can throw some light on this please...

Thanks in advance,